Apraxia and spatial inattention dissociate in left hemisphere stroke. (October 2015) - Timpert, David C.; Weiss, Peter H.; Vossel, Simone; Dovern, Anna; Fink, Gereon R.
Abstract: Theories of lateralized cognitive functions propose a dominance of the left hemisphere for motor control and of the right hemisphere for spatial attention. Accordingly, spatial attention deficits (e.g., neglect) are more frequently observed after right-hemispheric stroke, whereas apraxia is a common consequence of left-hemispheric stroke. Clinical reports of spatial attentional deficits after left hemisphere (LH) stroke also exist, but are often neglected. By applying parallel analysis (PA) and voxel-based lesion-symptom mapping (VLSM) to data from a comprehensive neuropsychological assessment of 74 LH stroke patients, we here systematically investigate the relationship between spatial inattention and apraxia and their neural bases. PA revealed that apraxic (and language comprehension) deficits loaded on one common component, while deficits in attention tests were explained by another independent component. Statistical lesion analyses with the individual component scores showed that apraxic (and language comprehension) deficits were significantly associated with lesions of the left superior longitudinal fascicle (SLF). Data suggest that in LH stroke spatial attention deficits dissociate from apraxic (and language comprehension) deficits. These findings contribute to models of lateralised cognitive functions in the human brain. Moreover, our findings strongly suggest that LH stroke patients should be assessed systematically for spatial attention deficits so that these can be included in their rehabilitation regime.